1979
DOI: 10.1007/bf01324740
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic hepatitis

Abstract: Seven patients with cardiovascular disease had clinical episodes and marked transaminase elevations that suggested viral hepatitis, but all had morphologic evidence (from liver biopsy or autopsy specimens) that documented centrilobular necrosis (ischemic hepatitis) with no evidence of viral or drug injury. Several also had moderate or marked passive congestion of the liver so the liver biopsies of 15 additional patients were retrospectively reviewed. In this latter group congestion alone was associated with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
76
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(84 citation statements)
references
References 11 publications
5
76
1
2
Order By: Relevance
“…The review of published series including at least 4 cases of HH 1,2,4,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] shows that exacerbation of CRF in patients free of left cardiac failure was the cause of HH in only 7 of 263 cases (2.6%). Moreover, clinical studies of asthmatic or CRF patients have reported normal or only slightly affected liver function tests.…”
Section: Discussionmentioning
confidence: 99%
“…The review of published series including at least 4 cases of HH 1,2,4,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] shows that exacerbation of CRF in patients free of left cardiac failure was the cause of HH in only 7 of 263 cases (2.6%). Moreover, clinical studies of asthmatic or CRF patients have reported normal or only slightly affected liver function tests.…”
Section: Discussionmentioning
confidence: 99%
“…The values rapidly return to normal, with recovery in less than one week. The generally accepted causes of ischemic hepatitis are congestive heart failure (10, 1 1) with or without shock, long-lasting shock without heart failure (trauma, dehydration, hemorrhage, burns, sepsis), heatstroke and rare cases of severe hypoxemia (9,10,(12)(13)(14)(15). The prognosis is usually determined by the initial cause.…”
Section: Discussionmentioning
confidence: 99%
“…30 The conclusion was that low oxygen tension in the blood rather than reduced oxygen delivery is the key factor that leads to ischemic hepatic necrosis when there is hypoxemia, [30][31][32] with contributions due to diminished hepatic blood flow and hepatic venous congestion, especially if the latter is severe as may occur in advanced right heart failure and constrictive pericarditis. 33 From the 1950s, the list of causes of acute ischemic liver injury was extended to include myocardial infarction 34,35 and cardiogenic shock, 36 left ventricular and biventricular failure, 33,37,38 and other reasons for shock like sepsis, acute pancreatitis, peritonitis, trauma, blackwater fever and following major surgery. [39][40][41][42] Centrizonal necrosis was the predominant histological lesion of hepatic ischemia in most series of cases in which liver histology was available, [31][32][33][34][35][36][37][38]43 occasionally midzonal necrosis occurs too, 33,44 whereas sinusoidal changes likely reflect concomitant passive congestion.…”
mentioning
confidence: 99%
“…33 From the 1950s, the list of causes of acute ischemic liver injury was extended to include myocardial infarction 34,35 and cardiogenic shock, 36 left ventricular and biventricular failure, 33,37,38 and other reasons for shock like sepsis, acute pancreatitis, peritonitis, trauma, blackwater fever and following major surgery. [39][40][41][42] Centrizonal necrosis was the predominant histological lesion of hepatic ischemia in most series of cases in which liver histology was available, [31][32][33][34][35][36][37][38]43 occasionally midzonal necrosis occurs too, 33,44 whereas sinusoidal changes likely reflect concomitant passive congestion. 33,45 The diagnosis maybe inferred when there is an abrupt and significant elevation of aminotransferases, 31,[35][36][37][38][46][47][48][49][50][51] usually without much in the way of alkaline phosphatase induction, and usually followed by normalization within 7-10 days.…”
mentioning
confidence: 99%
See 1 more Smart Citation